2015
DOI: 10.1155/2015/787805
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers, Progression to Dementia, and Effects on Amyloid Beta Peptide Production

Abstract: Previous epidemiologic studies suggest that antihypertensive drugs may be protective against cognitive decline. To determine if subjects enrolled in the University of Kentucky longitudinal aging study who used antihypertensive drugs showed diminished progression to dementia, we used a 3-parameter logistic regression model to compare the rate of progression to dementia for subjects who used any of the five common categories of antihypertensive drugs to those with similar demographic characteristics but who did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…In our previous studies we showed that nifedipine, a dihydropyridine calcium channel blocker, significantly decreased Aβ 1–42 production in an in vitro model [37]. In the course of those studies, we observed that nifedipine solutions became more effective after exposure to ambient light in the laboratory.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In our previous studies we showed that nifedipine, a dihydropyridine calcium channel blocker, significantly decreased Aβ 1–42 production in an in vitro model [37]. In the course of those studies, we observed that nifedipine solutions became more effective after exposure to ambient light in the laboratory.…”
Section: Resultsmentioning
confidence: 89%
“…In recent studies we demonstrated that AD subjects taking calcium channel blocker anti-hypertensives showed a slowed progression to dementia and that nifedipine in particular was effective in the decrease of Aβ production through decreases in PS-1 [37]. During the course of our studies of nifedipine, we identified a functionalized naphthyridine byproduct of the parent compound that appeared to have comparable efficacy on the inhibition of Aβ production in in vitro models.…”
Section: Introductionmentioning
confidence: 95%
“…16 In vitro studies show that blockade of calcium channels in neurons has a protective effect on "neurodegeneration" caused by β-amyloid. 10, 22 Nevertheless, it is not yet clear how to choose different types of CCBs for maximizing the neuroprotective benefits because of controversy surrounding the effects of CCB on cognitive function and reports that DHP CCBs would be more effective than non-DHP CCBs. Additionally, previous research has found that specific drugs, such as nitrendipine and nivaldipine, which can penetrate the blood-brain barrier, are more likely to affect cognitive function and improve "β-amyloid clearance".…”
Section: Discussionmentioning
confidence: 99%
“…In that study, a calcium channel blocker (CCB) was used and had a protective effect against dementia, especially Alzheimer's . Another similar study in Kentucky showed that CCBs could reduce dementia progression and minimize amyloid beta peptide formation without changes to cell viability . And in a study conducted on the predominantly male population of the Veterans Healthcare System in the United States, angiotensin receptor blockers achieved a significant reduction in the incidence and progression of AD and dementia compared to other cardiovascular drugs, including angiotensin converting enzyme inhibitors …”
Section: Blood Pressure Control Anti‐hypertension Agents and Cognitmentioning
confidence: 99%
“…81 Both calcium channel blockers (CCBs) and angiotensin receptor blockers (ARBs) are suggested to have a more pronounced protective effect than other anti-hypertensives. [82][83][84] In addition, the Syst-Eur trial also showed that anti-hypertensive medications can reduce stroke morbidity and mortality, and respondents may not be affected by dementia until at least 60 years of age. In that study, a calcium channel blocker (CCB) was used and had a protective effect against dementia, especially Alzheimer's.…”
Section: B Lood Pre Ssure Control Anti -Hyperten S I On Ag Ents mentioning
confidence: 99%